(untitled) (Journal of Current and Advance Medical Research, 2018)
Background: Clinical features are the important diagnostic tools for the detection of spontaneous intracerebral haemorrhage patients. Objective: The purpose of the present study was to see the clinical profiles of spontaneous intracerebral haemorrhage patients. Methodology: This cross-sectional study was conducted in the Department of Neurology at Dhaka Medical College and Hospital, Dhaka, Bangladesh from July 2012 to June 2014 for a period of two (2) years. Patients with spontaneous intracerebral haemorrhage who were admitted in the Departments of Neurology, Neurosurgery and Medicine at Dhaka Medical College and Hospital, Dhaka were selected as study population. Both male and female patients with the age group of ≥18 years, first ever spontaneous intracerebral haemorrhage and hospital admission within 48 hours of onset were included for this study. The clinical features of the study population were collected after admission of the patients like headache, hemiplegia or paresis, vomiting, and deterioration of consciousness, dysphasia, dysarthria and hemisensory loss. Result: Headache was observed the most frequent complaint in 81.0% (n=79) patients. Hemiparesis or hemiplegia was the most frequent focal neurological deficit in 69.0% (n=68) patients. Vomiting was common also 58.0% (n=57) patients. Twenty five (26.0%) respondents were presented with deterioration of consciousness. Dysphasia/aphasia was found in 15.0% patients. Convulsion was not a common presenting feature (7%). Conclusion: In conclusion headache, vomiting and deterioration of consciousness are the most common form of clinical feature of spontaneous intracerebral haemorrhage. Journal of Current and Advance Medical Research 2018;5(2):64-67